Information Searching Behaviour among UKM Cinematography Students Universitas Airlangga - Reghita, Lavena (Palimpsest: Jurnal Ilmu Informasi dan Perpustakaan, 2020)
Abstract Information seeking behavior among students of Cinematography to produce film work, is motivated by a gap that can lead to information needs based on the interests of students of Cinematography. Information needs of students Cinematography UKM is based on information needs based on environmental factors, namely information relating to the storyline. In addition, most students of Cinematography UKM produce films with the theme of one's experience. To meet these needs, students of UKM Cinematography have obstacles in the process of finding information, this proves that students of UKM Cinematography carry out the process of finding information. This study aims to determine the description of information seeking behavior in students of cinematographic, therefore this study uses the Wilson-Ellis Information Seeking Behavior Model. The method used in this research is quantitative descriptive method using total sampling technique. This study provides results regarding information related to the story line (65.6%) as the needs needed by Sinematogarfi UKM students, with the theme of one's experience (67.2%) which is done by conducting research (50.8%) first. The obstacle that is often experienced by students of UKM Cinematography is the difference of opinion (36.1%) when discussing with other UKM. For the references that are often used by students of UKM Cinematography, most of them are articles (73.8%) that are done at the browsing stage. In addition, seminars, workshops, film operations and film festivals (50.8%) are the preferred access for most students of Cinematography.Keywords: Information Searching Behavior; Information Needs; Student Cinematography AbstakPerilaku pencarian informasi di kalangan mahasiswa Sinematografi untuk menghasilkan karya film, dilatarbelakangi oleh adanya kesenjangan yang dapat menimbulkan kebutuhan informasi berdasarkan minat mahasiswa  Sinematografi. Kebutuhan informasi mahasiswa UKM Sinematografi didasarkan pada kebutuhan informasi yang didasarkan pada faktor lingkungan yaitu informasi yang berkaitan dengan jalan cerita. Selain itu, sebagian besar mahasiswa UKM Sinematografi memproduksi film bertema pengalaman sendiri. Untuk memenuhi kebutuhan tersebut mahasiswa UKM Sinematografi mengalami kendala dalam proses pencarian informasi, hal ini membuktikan bahwa mahasiswa UKM Sinematografi melakukan proses pencarian informasi. Penelitian ini bertujuan untuk mengetahui gambaran perilaku pencarian informasi pada mahasiswa sinematografi, oleh karena itu penelitian ini menggunakan Model Perilaku Pencarian Informasi Wilson-Ellis. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kuantitatif dengan menggunakan teknik total sampling. Penelitian ini memberikan hasil mengenai informasi terkait alur cerita (65,6%) sebagai kebutuhan yang dibutuhkan oleh mahasiswa UKM Sinematogarfi, dengan tema pengalaman seseorang (67,2%) yang dilakukan terlebih dahulu dengan melakukan penelitian (50,8%). Kendala yang sering dialami mahasiswa UKM Sinematografi adalah perbedaan pendapat (36,1%) saat berdiskusi dengan UKM lain. Untuk referensi yang sering digunakan mahasiswa UKM Sinematografi, sebagian besar berupa artikel (73,8%) yang dikerjakan pada tahap browsing. Selain itu, seminar, lokakarya, operasi film dan festival film (50,8%) merupakan akses yang disukai oleh sebagian besar mahasiswa Sinematografi. Kata Kunci: Perilaku Mencari Informasi; Kebutuhan Informasi; Sinematografi Mahasiswa